Teaching Children the Right Pronunciation in Preschool Education - Sharifjonova Fayoza Shuhrat qizi (Web of Journals Publishing, 2023)
This article describes the main stages of teaching preschool-age children the correct pronunciation, ways to teach children how to develop their speech to correct pronunciation in the exercise and how to teach them how to say words flawlessly.
Keywords: Preschool age, correct pronunciation, antonym, synonym, method.